Honor in German Literature - Fenwick Jones, George (UNC Studies in the Germanic Languages and Literatures, 1959)
Originally published in 1959, this first scholarly study of the origin and development of the concept of honor in German literature traces its role from ancient Germanic to modern works and shows how the transformation from external to internal conceptions of honor were influenced by Christian and Stoic ideals.